Предмет: Алгебра,
автор: allaroze4763
Вычислите:
√(a+b)^2
√(8-√7)^2+√(2-√7)^2
(3√3+√12)^2
3^5*5^4/15^3
Ответы
Автор ответа:
0
√(a+b)^2=a+b
√(8-√7)^2+√(2-√7)^2=8-√7+2-√7=10-2√7
(3√3+√12)^2=27+6√36+12=39+√36
=
=3^2*5=9*5=45
√(8-√7)^2+√(2-√7)^2=8-√7+2-√7=10-2√7
(3√3+√12)^2=27+6√36+12=39+√36
Похожие вопросы
Предмет: Математика,
автор: Bamboozled
Предмет: История,
автор: adiyagalymzhanova201
Предмет: Химия,
автор: itachi200711
Предмет: Математика,
автор: лерахру
Предмет: Биология,
автор: nadyavigovska